Single-cell Sequencing Reveals Key Biological Insights into Intervertebral Disc Development and Degeneration - Yu, Chaorong; Yang, Wei; Wang, Yanyan; Zhang, Yujie (Current Molecular Medicine, 2026)
Intervertebral disc degeneration (IDD) is a common spinal disease that imposes a significant economic burden on healthcare systems. Understanding the biological processes involved in IDD development and degeneration is critical for developing potential therapeutic approaches. Single-cell RNA sequencing (scRNA-seq) technology has revolutionized our understanding of cellular heterogeneity at the single-cell level and provided profound insights into the transcriptional landscape of IDD. This review provides an overview of research progress on the cellular biological characteristics of IDD occurrence and degeneration using scRNA-seq. It systematically summarizes the applications and key findings of scRNA-seq in subtyping cell populations, detecting transcriptomic changes, regulating signaling pathways, and elucidating cell-cell interactions in IDD. Additionally, it emphasizes the potential role of scRNA-seq in maintaining and repairing intervertebral disc tissues, from both preventive and therapeutic perspectives. In summary, this study underscores the extensive application of scRNA-seq in degenerative disc research and provides a foundation for future investigations and potential treatment strategies.
Keywords: nucleus pulposus